Problemy definicyjne w nauczaniu i badaniu khmerskiej grzeczności językowej - Long-Kucharczyk, Setha (Investigationes Linguisticae, 2010)
The author of this article refers to a set of vital definitions one has to take into consideration in teaching and reserarching language politeness. Etnolinguistic analyze of language savoir vivre is impossible vithout reference to key anthrolological notions such as culture, cultural pattern, education. The basis used in this article to reconcile various antrophological schools is the theory of Geert Hofstede who proposes wide and simple definition of culture, treated as a “‘collectively programmed mind” that differs one group or category of people from other. Being a Khmer naturalized in Polad, the author is fucused on pupularization of Khmer language and culture in her second motherland. Having a sense of mission to provide Polish users of Khmer language with cultural competence that will anable them to be seen in Cambodia as polite people, the author compares Polish and Khmer colloquial understanding of politeness. She also refers to Polish linguistic works on language politeness, looking for definitional solutions that will help teach and analyze language savoir vivre of the Khmers